Sugared water consumption by adult offspring of mothers fed a protein-restricted diet during pregnancy results in increased offspring adiposity: the second hit effect. Issue 4 (14th October 2013) - Cervantes-Rodríguez, M.; Martínez-Gómez, M.; Cuevas, E.; Nicolás, L.; Castelán, F.; Nathanielsz, P. W.; Zambrano, E.; Rodríguez-Antolín, J.
Abstract : Poor maternal nutrition predisposes offspring to metabolic disease. This predisposition is modified by various postnatal factors. We hypothesised that coupled to the initial effects of developmental programming due to a maternal low-protein diet, a second hit resulting from increased offspring postnatal sugar consumption would lead to additional changes in metabolism and adipose tissue function. The objective of the present study was to determine the effects of sugared water consumption (5 % sucrose in the drinking-water) on adult offspring adiposity as a 'second hit' following exposure to maternal protein restriction during pregnancy. We studied four offspring groups: (1) offspring of mothers fed the control diet (C); (2) offspring of mothers fed the restricted protein diet (R); (3) offspring of control mothers that drank sugared water (C-S); (4) offspring of restricted mothers that drank sugared water (R-S). Maternal diet in pregnancy was considered the first factor and sugared water consumption as the second factor – the second hit. Body weight and total energy consumption, before and after sugared water consumption, were similar in all the groups. Sugared water consumption increased TAG, insulin and cholesterol concentrations in both the sexes of the C-S and R-S offspring. Sugared water consumption increased leptin concentrations in the R-S females and males but not in the R offspring. There was also an interaction between sugared water and maternal diet in males. Sugared water consumption increased adipocyte size and adiposity index in both females and males, but the interaction with maternal diet was observed only in females. Adiposity index and plasma leptin concentrations were positively correlated in both the sexes. The present study shows that a second hit during adulthood can amplify the effects of higher adiposity arising due to poor maternal pregnancy diet in an offspring sex dependent fashion.